PREVALENCE AND DETERMINANTS OF INTIMATE PARTNER VIOLENCE TOWARDS FEMALE STUDENTS OF THE UNIVERSITY OF IBADAN, NIGERIA. (2012)
Intimate Partner Violence (IPV) is pervasive, but under-reported by victims because of the associated stigma and fear of reprisals. In Nigeria, there is paucity of information on IPV burden among female university students. This study was therefore designed to assess the prevalence and determinants of IPV experienced by female students in the University of Ibadan, Nigeria. The study was cross-sectional in design. A four-stage sampling technique was used in selecting the female halls (two undergraduate and one postgraduate), blocks, rooms, and an occupant selected by balloting in each room. A total of 1,100 undergraduate and 255 postgraduate female students were selected. A 43-item self-administered structured questionnaire was used to collect data on the sociodemographic characteristics, prevalence, types, determinants, awareness, and health consequences of IPV. Data were analysed using descriptive statistics and logistic regression at p = 0.05. The mean age of the respondents was 22.8±3.9 years (postgraduate mean: 24.3±3.2 years; undergraduate mean: 20.1±3.2 years) and majority (93.8%) were single. Respondents comprised Yoruba (61.7%), Igbo (24.6%), Hausa (3.6%) and others (10.1%). The proportions of respondents who smoked, consumed alcohol and had a family history of IPV were 6.6%, 22.8% and 26.9% respectively. The life-time prevalence of IPV was 42.3% (postgraduate: 34.5%; undergraduate: 44.1%) and those for psychological, physical and sexual IPV were 41.8%, 7.9% and 6.6% respectively. Majority (61.9%) of the respondents who were aware of IPV did not experience it. Respondents who were less likely to have experienced IPV were postgraduate (OR= 0.64; 95% CI: 0.46-0.87), and married (OR= 0.53; 95% CI: 0.35-0.78) students. Life-time prevalence of IPV was higher among the undergraduates (OR=3.82; 95% CI: 1.08-13.40); smokers (OR= 2.46; 95% CI: 1.58-3.83); alcohol consumers (OR= 2.36; 95% CI: 1.82- 3.06 ); and those with family history of IPV (OR= 2.40; 95% CI: 1.88- 3.07). Recent experience (within the last one year) of violence was also more frequently reported by respondents who had a UNIVERSITY OF IBADAN LIBRARY vi previous history of physical (62.5%) (OR= 2.65; 95% CI: 2.02-3.49) and sexual (53.2%) (OR= 1.63; 95% CI:1.12-2.35) violence. Injuries were sustained by sixty (4.4%) of the IPV victims and these included minor abrassions (60.7%), sprains (17.9%), and facial injuries (15.4%). Adverse effects of IPV on academic performance were reported by 10.3% of victims and these included loss of concentration (71.4%), interruption of studies (17.9%), loss of self-esteem (6.4%) and school absenteeism (4.3%). Majority (60.9%) of the victims of IPV did not seek help. Those who sought help went mainly to religious leaders (12.5%), hospitals (10.5%) and family members (4.9%). The prevalence of intimate partner violence among the female students of the University of Ibadan was high, and the major predicting factors were low level of awareness, family history and previous history of physical and sexual violence. There is the need to design interventions to address modifiable risk factors like smoking and alcohol consumption, and encourage health seeking in order to reduce vulnerability and related health consequences. Keywords: Intimate Partner Violence, University female students, Life-time experience. Word Count: 479